The Meaning and Utilization of Plants in Wedding Ceremonies: An Ethnobotanical Study of the Community in Sungai Deras Village, East Air Hangat District, Kerinci - Alpita Juliarna; Damris M; Revis Asra; Ilham Falani (SENTRI: Jurnal Riset Ilmiah, 2025)
This study is qualitative research with a descriptive design focusing on ethnobotanical analysis within the traditional wedding ceremonies of the Kerinci community, particularly in Sungai Deras Village. The primary objective of this study is to classify and inventory the diversity and types of flora utilized in wedding rituals at the research site. It aims to document the plant species involved in traditional wedding practices in Sungai Deras Village and to thoroughly analyze the philosophical semantics of their use as representations of local wisdom. The research methodology employs purposive sampling to select key informants, consisting of traditional leaders, religious figures, and community representatives. Data were collected through direct observation of the rituals, in-depth interviews, and documentation. The findings reveal five main plant components (betel leaf, areca nut, gambier, lime, and tobacco) that collectively shape the ethical pillars of the ceremony. Betel leaf (Piper betle) represents purity of intention and communication; areca nut (Areca catechu L.) symbolizes dignity and hopes for prosperity; gambier (Uncaria gambir) reflects kinship solidarity; lime (calcium/lime, functioning as a component supporting D. aromatica) signifies customary foundations and noble values; and tobacco (Nicotiana tabacum L.) conveys social approval from cultural authorities. The use of these plants does not contradict Islamic teachings the predominant religion of the community and its traditional leaders because it aligns with the principle “adat basandi syara’, syara’ basandi kitabullah”